1992
DOI: 10.1108/09513579210017389
|View full text |Cite
|
Sign up to set email alerts
|

Some Feminisms and Their Implications for Accounting Practice

Abstract: Uses Harding′s 1986 book. The Science Question in Feminism, as a framework for examining the implications of some feminisms for accounting. First explores feminist empiricism which challenges the exclusion of women from prominent professions. Second, addresses feminist postmodernism, which explores the differences among women and contends that no over‐arching feminist theory can be found. Third, analyses the feminist standpoint. Advocates that the current masculine system be replaced by one that is infused wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 0 publications
0
49
0
2
Order By: Relevance
“…As a result, there is little information on ethnic minority women accountants and their impact on the practices and culture of accounting, as well as the organizations in which they work and the profession as a whole [261. In this paper, I have challenged the notion of accounting practice as a western-masculine discipline reflecting white-male values and thinking (Hammond and Oakes, 1992). The findings from my study have demonstrated that the experiences of Chinese women accountants within the western-masculine accounting environment are a reflection of the differences between men and women and western culture and Chinese culture.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…As a result, there is little information on ethnic minority women accountants and their impact on the practices and culture of accounting, as well as the organizations in which they work and the profession as a whole [261. In this paper, I have challenged the notion of accounting practice as a western-masculine discipline reflecting white-male values and thinking (Hammond and Oakes, 1992). The findings from my study have demonstrated that the experiences of Chinese women accountants within the western-masculine accounting environment are a reflection of the differences between men and women and western culture and Chinese culture.…”
Section: Resultsmentioning
confidence: 77%
“…The second theoretical model views race/ethnicity and gender as parallel phenomena that can be understood in a similar way (Hacker, 1951;Grady, 1977;Yarkin et al, 1982;Smith and Stewart, 1983; II Hammond and Oakes, 1992). There are some sociological and psychological parallels between ethnic minorities and women who both have long been victims of institutionalized racism and/or sexism.…”
Section: Interview Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the topic of gender relations in accountancy firms remains under-researched (Anderson-Gough et al, 2005;Czarniawska, 2008). Hammond and Oakes (1992), Haynes (2008a) and Lehman (1992) present overviews of the theories and methodologies that are used in the academic accountancy articles that address gender issues, and they discuss their implications on research. Hammond and Oakes (1992) outlined three major streams of feminist theory and their applications to accountancy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interestingly, there is a notion that changes in the number of women in a particular profession would change the direction of the profession (Hammond and Oakes, 1992).…”
Section: Introductionmentioning
confidence: 99%